The Problem of Governing
XXIII, 284 p. 3 illus.
Keywords: This book provides an appreciation of the work of renowned scholar Richard Rose. Over a career spanning more than six decades, Rose has explored a vast range of subjects related to British, American and comparative politics. His work, however, has always been concerned with an underlying theme: governing modern societies in changing times. Celebrating Rose's career which has shaped postwar political science in decisive ways, this volume examines issues, debates and lines of research stimulated by his work. Chapters are organized thematically under five headings central to his research: parties and elections, political institutions, public policy, governing at multiple levels, and trust and legitimacy. The book demonstrates that politics cannot be reduced to economics, the actions of individuals, predictive science or functional determinism, but has its own logic and modes of justification. It will appeal to scholars and students of politics, public policy and governance. Michael Keating is Emeritus Professor at the University of Aberdeen, UK Ian McAllister is Distinguished Professor of Political Science at the Australian National University, Australia Edward C. Page is Sidney and Beatrice Webb Professor of Public Policy at the London School of Economics and Political Science, UK B. Guy Peters is Maurice Falk Professor of American Government at the University of Pittsburgh, USA.